ANALISIS DAN ARAHAN PENGEMBANGAN RUANG TERBUKA HIJAU DALAM MENDUKUNG GREEN CITY KOTA UNGARAN KABUPATEN SEMARANG - Antonius Dwi Yunianto, Santun R. P. Sitorus, dan Khursatul Munibah (Universitas Gadjah Mada, 2016)
The provision of Green Open Space (GOS) constitutes an important need for city and as a mandate ofthe Law on Spatial Planning. Ungaran city currently has the width of public GOS under 20%. It makesUngaran city has not yet qualified to become a Green City. The objectives of this study are to identify andanalyze the width and distribution of GOS existing condition; to analyze the needs of Ungaran’s GOSin order to meet the specified conditions of prevailing law; to arrange the plan of GOS based on GreenPlanning concept; and to arrange the design of GOS based on Green Design concept. The analysis willbe conducted by using Patch Analysis method. The analysis of GOS is based on the inhabitant’s needand the wide area, and the Analytic Hierarchy Process (AHP). The GOS mapping result of Ungarancity is 2.190,66 ha which consists of private GOS (2.112,74 ha) and public GOS (77,92 ha). Based onthe total projection of population in 2032, the public GOS need is 292,41 ha. Whereas the needs ofpublic GOS based on the 20% from wide area (612,17 ha). The direction of public GOS developmentbased on green planning is divided into three alternatives, first, based on the balance distribution ofGOS within the area, and land use priority; second, based on the balance distribution of GOS, land usepriority, distance to the residence, minimum width of 250m2, and the complexity of landform; third,based on the consideration of the spatial patterns and regional asset authority. The direction of publicGOS development is based on green design approach to divide the design based on necessity activityand function patterns of public GOS.